2012
DOI: 10.1002/mrm.24427
|View full text |Cite
|
Sign up to set email alerts
|

A 64‐channel 3T array coil for accelerated brain MRI

Abstract: A 64-channel brain array coil was developed and compared to a 32-channel array constructed with the same coil former geometry in order to precisely isolate the benefit of the two-fold increase in array coil elements. The constructed coils were developed for a standard clinical 3T MRI scanner and used a contoured head-shape curved former around the occipital pole and tapered in at the neck to both improve sensitivity and patient comfort. Additionally, the design is a compact, split-former design intended for ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
216
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(223 citation statements)
references
References 27 publications
7
216
0
Order By: Relevance
“…However, both coils showed similar SNRs at the anterior region. Previous studies have shown that an increase in the number of coil elements improves the SNR near the coil surface [21,23]. Our results, therefore, suggest that many elements are arranged in the posterior region of the 32-channel coil.…”
Section: Discussionsupporting
confidence: 39%
See 3 more Smart Citations
“…However, both coils showed similar SNRs at the anterior region. Previous studies have shown that an increase in the number of coil elements improves the SNR near the coil surface [21,23]. Our results, therefore, suggest that many elements are arranged in the posterior region of the 32-channel coil.…”
Section: Discussionsupporting
confidence: 39%
“…Generally, the SNR in regions distant from the coil surfaces is independent of the number of coil elements [1]. Wiggins et al and Keil et al have also shown that an increase in the number of coil elements does not result in an improvement in the central SNR [21,23]. On the other hand, some previous reports on custom coils have shown that a narrower inner space of the coil results in an increase in the SNR at the center of a phantom [20,22] and a narrower inner space of the coil permits the surfaces of the coil to be closer to the center of the object.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A custom-made 64-channel phased array coil was used for signal reception (Keil et al, 2013). We utilized probabilistic tractography for quantitative connectivity measurements and deterministic tractography for qualitative visualization of the pathways by which streamlines travel between seed and target nodes (Edlow et al, 2012;McNab et al, 2013).…”
Section: Diffusion Data Acquisition and Processingmentioning
confidence: 99%